Annual World Bank Conference on Development Economics--Europe 2005 : Are We on Track to Achieve the Millennium Development Goals? - Bourguignon, François (Washington, DC: World Bank and Oxford University Press, 2012)
This Sixth Annual World Bank Conference on Development Economics, one of the world's best-known series of conferences, aims at the presentation, and discussion of new knowledge on development. The theme of the conference was "Doha, Monterrey, and Johannesburg: Are We on Track to Achieve the Millennium Development Goals (MDGs)?" The conference provides a forum for the world's leading development thinkers to share new knowledge, and ideas. This Conference was designed to look at how four flows (flows of people, capital, aid, and trade) link developed and developing countries. Discussions show not only where some of the main opportunities are in each of these four areas, but also where the main blockages are, and what the real risks are-both when flows accelerate, and when flows dry up. Notably, it was argued that developed countries should have the courage to push globalization further: Europe, like the United States, is protectionist, and as long as it stays that way, there can be no real free trade on the global level. It was proposed a political counterpart to what exists on the economic level be created, i.e., to replace the G-8 of rich countries, with a G-8 of local and regional groups. Such a G-8 would grant a legitimate place to the South, and could serve as a forum for consultation among various continental structures - African Union, Mercosur, the European Union, the Association of Southeast Asian Nations, and the North American Free Trade Agreement. Such a G-8 would not only contribute to improved relations between various parties, but would also encourage various regions to intensify their cooperation. Similarly, the creation within the United Nations of an Economic, Social, and Environmental Security Council was proposed, which would form the new framework for globalization, thus monitor implementation of conclusions from large conferences, and, coordinate the major international institutions such as the World Trade Organization, International Labor Organization, International Monetary Fund, and World Bank. Redistribution through official development assistance is extremely limited, and it is cancelled out by rich countries' restrictions that limit poor countries' market access. It is argued that the objective of aid is not to redistribute income today, in order to increase immediate consumption; the objective is to transfer growth potential from rich countries to poor countries. Trade flows, capital flows, and migration flows could also be seen as influencing the growth potential of the poorest countries. Maximizing this potential is essential for a future unambiguous, improvement in the world distribution of income. Furthermore, an alternative way forward for the Doha Round is presented, based on the principles of social justice and economic analysis. The World Trade Organization (WTO) needs to establish a source of impartial, and publicly available analysis of the effects of various initiatives on different countries.